Public Relations Marketing Strategy in Building Brand Awareness through Instagram: Habibu Cake Case Study - Wulan Sari Putri; Lies Utami Efni Safitri (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid growth of social media, particularly Instagram, has transformed Marketing Public Relations (MPR) strategies for small and medium-sized enterprises (SMEs) in Indonesia’s increasingly competitive digital landscape. However, Habibu Cake, a local artisan dessert SME based in Medan, North Sumatra, continues to face challenges in optimizing brand awareness despite its active use of Instagram, while scholarly attention to the role of MPR in building brand awareness among culinary SMEs in Medan remains limited. This study aims to analyze the MPR strategies implemented by Habibu Cake through Instagram and examine their role in strengthening brand awareness. A qualitative descriptive method with a single case study approach was employed. Data were collected through in-depth interviews with five consumers and active followers of the @habibu.cake Instagram account, non-participatory observation of the account from January to March 2024, and documentation analysis of published content from 2022 to 2024. The findings reveal three interconnected MPR pillars: structured and authentic content creation based on five content pillars, strategic endorsement involving 19 local micro-influencers across 28 campaigns, and consistent community engagement generating approximately 340 user-generated content items per month. These strategies contributed to substantial growth, including a 477% increase in followers, a 589% increase in average reach per post, a 124% increase in engagement rate reaching 4.7%, a 656% increase in monthly user-generated content, and a 797% increase in profile visits. The study concludes that a consistent, authentic, and community-driven MPR approach on Instagram is highly effective in progressively building brand awareness for local culinary SMEs. These findings contribute to digital marketing communication literature by offering a three-pillar MPR model and provide practical implications for local culinary SMEs in Indonesia to develop effective, adaptive, and sustainable Instagram-based brand communication strategies.